From coexistence to conquest : international law and the origins of the Arab-Israeli conflict, 1891-1949 - Kattan, Victor (Pluto Press, 2009)
From Coexistence to Conquest seeks to explain how the Arab-Israeli conflict developed by looking beyond strict legalism to the men behind the policies adopted by the Great Powers at the dawn of the twentieth century. It argues that Zionism was adopted by the British Government in its 1917 Balfour Declaration primarily as an immigration device and that it can be traced back to the 1903 Royal Commission on Alien Immigration and the Alien's Act 1905. The book contains a legal analysis of the 1915-6 Hussein-McMahon correspondence, as well as the Balfour Declaration, and takes a closer look at the travaux préparatoires that formed the British Mandate of Palestine. It places the violent reaction of the Palestine Arabs to mass Jewish immigration in the context of Zionism, highlighting the findings of several British commissions of inquiry which recommended that Britain abandon its policy. The book also revisits the controversies over the question of self-determination, and the partition of Palestine. The Chapter on the 1948 conflict seeks to update international lawyers on the scholarship of Israel's 'new' historians and reproduces some of the horrific accounts of the atrocities that took place from newspaper reports, UN documents, and personal accounts, which saw the expulsion and exodus of almost an entire people from their homeland. The penultimate chapter argues that Israel was created through an act of conquest or subjugation. The book concludes with an analysis of the conflict, arguing that neither Jews nor Arabs were to blame for starting it. --From publisher's description.